2010
DOI: 10.1002/art.27595
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microfocal computed tomography and micro–magnetic resonance imaging evaluation of antiresorptive and antiinflammatory drugs as preventive treatments of osteoarthritis in the rat

Abstract: Objective. To determine whether treatment with an antiresorptive drug in combination with an antiinflammatory drug reduces periarticular bone and soft tissue adaptations associated with the progression of posttraumatic secondary osteoarthritis (OA).Methods. We used in vivo microfocal computed tomography (micro-CT) to map bony adaptations and in vivo micro-magnetic resonance imaging (micro-MRI) to examine joint inflammation in a rat model of surgically induced OA secondary to knee triad injury. We examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 37 publications
(46 reference statements)
4
58
2
Order By: Relevance
“…But more and more researches have demonstrated that increasing subchondral bone mass was beneficial to the reduction of cartilage degradation, such as ALN administration in OA, hip osteonecrosis, or other diseases in different models [9,[35][36][37]. The present study was focused on the examination of ALN effects on subchondral bone quality to further evaluate the relationship between subchondral bone and cartilage degeneration in OA progress.…”
Section: Discussionmentioning
confidence: 99%
“…But more and more researches have demonstrated that increasing subchondral bone mass was beneficial to the reduction of cartilage degradation, such as ALN administration in OA, hip osteonecrosis, or other diseases in different models [9,[35][36][37]. The present study was focused on the examination of ALN effects on subchondral bone quality to further evaluate the relationship between subchondral bone and cartilage degeneration in OA progress.…”
Section: Discussionmentioning
confidence: 99%
“…This was used to create 3D models of osteophytic bone for quantitative volumetric assessment. Osteophyte severity from 3D μCT models of the tibia for each knee was graded on a 4 point scale by three investigators (RDLV, TJF and AGB) in a blinded fashion, where 0 = no observed osteophyte, 1 = local and less severe osteophytes, 2 = widespread, but moderately severe osteophytes and 3 = widespread and very severe osteophytes (Jones et al , 2010; Shirai et al , 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The coefficients of variation were 2.0% (BV/TV), 1.1% (TbN), 0.66% (TbTh), and 1.30% (TbSp) for morphometric parameters. 38 Cortical bone volume fraction (BV/TV; %) and cortical thickness were also calculated using the Skyscan software CTan.…”
Section: Bone Microarchitecture Assessment By Kctmentioning
confidence: 99%